Five new species of Meteorus Haliday (Hymenoptera: Braconidae: Euphorinae) from Brazil - Almeida, Luis Felipe Ventura De; Dias, Angélica Maria Penteado (Zootaxa, 2015)
Meteorus Haliday, 1835 (Hymenoptera: Braconidae) is a cosmopolitan genus with around 340 species described, all koinobiont endoparasitoids of Coleoptera or Lepidoptera larvae, and several of its hosts are pest insects. Previously to this work only two species were described from Brazil, M. eaclidis Muesebeck and M. townsendi Muesebeck. Five new species of Meteorus are here described: M. atlanticus n. sp., M. ferruginosus n. sp., M. itatiaiensis n. sp., M. monoceros n. sp., and M. strigatus n. sp. Three species are recorded for the first time from Brazil: M. jerodi Aguirre & Shaw, M. laphygmae Viereck and M. megalops Zitani.